Gypsum efflorescence on clay brick masonry: Field survey and literature study. (15th June 2015) - Chwast, Jacek; Todorović, Jelena; Janssen, Hans; Elsen, Jan
Highlights: 28 Belgian cases of persistent masonry efflorescence were investigated. Gypsum is the major persistent efflorescence component. The formation mechanism is related to moisture transport and not to air pollution. Both brick and mortar can be the source of gypsum efflorescence. Many aspects remain hypothetical, rising important research questions. Abstract: Belgian masonry facades are being increasingly affected by unsightly persistent efflorescence. This results in disappointed customers and consequently creates a threat for the brick industry. Our paper presents a field survey and literature review on the topic. An investigation of Belgian cases reveals gypsum abundance in the deposit. The specific characteristics and literature review indicate masonry as the source and moisture transfer as the transport mechanism. However, there is currently no sound explanation for the crystallisation of gypsum on the surface and its only recent occurrence. One hypothesis points at mortar additives, which may affect the transport and crystallisation of gypsum.